The CooQis Box / Fariesha Syazwani Azmir and Salmiza Ainatasya Mohd Zurimi - Azmir, Fariesha Syazwani; Mohd Zurimi, Salmiza Ainatasya (2022)
The CooQis Box by FS is one of the agent of The CooQis Box Enterprise. We sell melted cooqis and soft cookies with variety of toppings. The business is own and run by 2 individuals, which are Fariesha Syazwani Binti Azmir and Salmiza Ainatasya Binti Mohd Zurimi. Our business is based in Cheras, Selangor. The CooQis Box by FS always strive to provide the highest standards of care to our customer and it will be disapointing if we don't. Our target audience is for those who enjoy eating desert especially cookies and chocolate in Malaysia. We are using premium products to bake our cookies to serve our customer the best from the best among the cookies that they have tried. We are using facebook as our main platform for marketing purposes. We noticed that Facebook has broader engagement with customers as compare with other social media platforms. The CooQis by FS uses both hard and soft sells to attract and engange with our lovely customers. For ordering purposes, we are using WhatsApp as it is widely use by the people in Malaysia